2014
DOI: 10.1038/jid.2013.366
|View full text |Cite
|
Sign up to set email alerts
|

A Meeting of Two Chronobiological Systems: Circadian Proteins Period1 and BMAL1 Modulate the Human Hair Cycle Clock

Abstract: The hair follicle (HF) is a continuously remodeled mini organ that cycles between growth (anagen), regression (catagen), and relative quiescence (telogen). As the anagen-to-catagen transformation of microdissected human scalp HFs can be observed in organ culture, it permits the study of the unknown controls of autonomous, rhythmic tissue remodeling of the HF, which intersects developmental, chronobiological, and growth-regulatory mechanisms. The hypothesis that the peripheral clock system is involved in hair c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 92 publications
(173 reference statements)
2
115
0
Order By: Relevance
“…This observation is in agreement with previous reports using different cell types, as well as mice cartilage 8, 22, 30, 4447 . We identified lower expression levels of multiple circadian rhythm genes by genome wide RNA sequencing in OA, and bioinformatics analysis revealed that circadian rhythm is the most dysregulated pathway in human OA cartilage.…”
Section: Discussionsupporting
confidence: 94%
“…This observation is in agreement with previous reports using different cell types, as well as mice cartilage 8, 22, 30, 4447 . We identified lower expression levels of multiple circadian rhythm genes by genome wide RNA sequencing in OA, and bioinformatics analysis revealed that circadian rhythm is the most dysregulated pathway in human OA cartilage.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, rhythmic clock gene expression was reported in another constantly remodeling human organ, the hair follicle. Disruption of the clock components Per1 , Bmal1 , or Clock with RNAi significantly prolongs the anagenic phase of intensive epithelial proliferation, suggesting that the clock is required for a normal progression of the hair cycle [74]. Multiple studies provide evidence that the molecular clockwork is important for normal stem cell function in other organs also, such as brain, blood, and intestine [75].…”
Section: Physiological Significance Of the Clock-cell Cycle Couplingmentioning
confidence: 99%
“…Indeed, clock genes modulate the human hair cycle clock independently of the brain suggesting that a peripheral hair clock also exists [44, 45]. Clock genes and their products are also co-expressed with stem cells markers in hair and perturbations of circadian clocks result in changes in hair follicle renewal [46].…”
Section: Clock Genes and Stem Cellsmentioning
confidence: 99%